Odpowiedź :
a)
x^2 + 3x = 2x + 6
2^2 + 3 * 2 = 2 * 2 + 6
= 4 + 6 = 4 + 6
10 = 10
Liczba spełnia równanie
b)
x^2 - 4x = 6 - x
-1^2 - 4 * (-1) = 6 - (-1)
1 - (-4) = 6 + 1
1 + 4 = 7
5 ≠ 7
Liczba nie spełnia równania
c)
2x - 13 = x^2 + 5
2 * (-3) - 13 = -3^2 + 5
-6 - 13 = 9 + 5
-19 ≠ 14
Liczba nie spełnia równania
d)
x^3 + 4x^2 = x(x + 2)
1^3 + 4 * 1^2 = 1 * (1 + 2)
1 + 4 * 1 = 1 * 3
1 + 4 = 3
5 ≠ 3
Liczba nie spełnia równania
e)
[tex]\frac{2}{x^2 + 2} = \frac{x}{6}\\\\\frac{2}{2^2 + 2} = \frac{2}{6}\\\\\frac{2}{4 + 2} = \frac{1}{3}\\\\ \frac{2}{6} = \frac{1}{3}\\\\\frac{1}{3} =\frac{1}{3}[/tex]
Liczba spełnia równania
f)
3^x - 2 = (x + 2)^2
3^3 - 2 = (3 + 2)^2
27 - 2 = 5^2
25 = 25
Liczba spełnia równanie